Factors contributing to unsuccessful rehabilitation: a case study investigating the rehabilitation practices in Opencast Coal Mines in the Mpumalanga Province, South Africa - Gule, Nontobeko (Department of Chemical Engineering, 2021)
The coal mining industry has played a significant role in the development of the South African economy. Coal supplies about 70% of South Africa's primary energy and is likely to remain the country's major source of energy despite the increasing trends towards renewable energy. Even though the industry has significantly contributed to the development of the country, it has also caused significant impacts on the environment with concomitant socio-economic impacts. Historically, once a coal measure was exhausted, mining companies would cease production and abandon the mines without proper rehabilitation of the environmental degradation caused by their mining activities. As a result of this, the South African Government introduced mining and rehabilitation legislation to mitigate the environmental and associated socio-economic impacts of mining. Rehabilitation guidelines for opencast coal mines were developed to provide detailed guidance for achieving successful and sustainable rehabilitation, to mitigate pollution post-mining. Despite the more stringent legislative framework and the development of international standard rehabilitation guidelines, successful mine rehabilitation remains a challenge. This research project aims to develop a better qualitative understanding of the status, challenges, gaps and opportunities pertaining to current rehabilitation practices in the case of opencast coal mines in the Mpumalanga Province of South Africa, and in so doing, establish the contributing factors of unsuccessful rehabilitation. The dissertation draws on a comprehensive review of published literature and an analysis of semi-structured interviews with rehabilitation experts. The study found that the current rehabilitation practices in the Mpumalanga opencast mines are not to the standard required by the legislative framework nor prescribed by rehabilitation guidelines. As such, the current rehabilitation practices are not yielding successful and sustainable rehabilitation. According to the findings, the rehabilitation practices are hampered by physical and non-physical systemic challenges that thwart the achievement of successful rehabilitation. The study analysis shows that shortcomings in the application and enforcement of the legislative framework contributes to the legislation not achieving its intended objectives as well as the development of other physical and non-physical systemic challenges that hamper the achievement of successful rehabilitation.